STUDY OF OPTIMIZATION AND NORMALIZATION OF VILLAGE NATURAL RIVER BUILDING REJO TENGGARONG DISTRICT, KUTAI KARTANEGARA - PUTRA, RUSMAN ARTA (KURVA S JURNAL MAHASISWA, 2020)
In the area of Bangun Rejo Village in Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan Province is an area that often experiences flooding and is a major problem for Bangun Rejo Village Residents. Several factors cause flooding due to the not yet maximum capacity of river channels and sedimentation to drain incoming water. The existing dimensions that need to change in order to smooth the flow of river water. The method used to calculate the design rainfall is using the Gumbel method, the Log person type III method, and for the design discharge calculation using the Nakasayu Synthetic Unit Hydrograph (HSS) method. From the results of the design discharge calculations 2, 5, 10, and 25 years obtained design discharge for each river channel to be investigated, in the field measurements each river channel is calculated and obtained river dimensions and river capacity discharge, from existing analysis results river discharge is not able to accommodate the design discharge, the conclusion is needed to change the dimensions of the river for the next 25 years.